Reimagining the birth of the Messiah and his forerunner in Luke's gospel: a sociorhetorical interpretation - Smit, David C (Department of Religious Studies, 2020)
This thesis investigates Luke’s portrayal of the subordination of John, the son of Zechariah and Elizabeth, to Jesus the Messiah in Luke 1–2. A detailed analysis of the opening-middleclosing textures of the Lukan text brings to the fore a clear structural juxtaposing and interweaving of the birth and infancy narratives of John and Jesus. The exercise provides the organising framework for the thesis. An in-depth sociorhetorical interpretation of these texts is then undertaken. The rhetography and rhetology of the infancy narrative of John are first explored in detail, beginning with the annunciation to Zechariah in 1:5–25, continuing with the account of his birth in 1:57–66, and closing with Zechariah’s resultant doxology in 1:67–80. A similar analysis is then undertaken of the infancy narrative of Jesus, beginning with the annunciation to Mary in Luke 1:26–38, continuing with the account of his birth and the angelic doxology and shepherds’ tribute in 2:1–21, and closing with his presentation at the temple in 2:22–40. This closing text portion is identified as the closing texture of Luke’s juxtaposing and weaving together of the two birth and infancy narratives. The process incorporates an analysis of the ideological texture, which emerges in Luke’s development of these two narratives. The ideological texture manifests primarily in the emergence of an asymmetrical honour-power relationship between John and Jesus. A range of rhetorical strategies are identified as used by Luke to enhance the ideological texture, which in turn emphasises the surpassing honour and power of Jesus over and against that of John, his forerunner. My thesis makes a contribution to Lukan research by clarifying Luke’s emergent ideological texture in the rhetoric of his two birth and infancy narratives. The use of the sociorhetorical interpretive analytic provides a thick description of the rhetoric of these two narratives, while engaging in conversation with cultural and scribal intertexture from the Jewish Scriptures and Second Temple Judaism. The dialogical nature of sociorhetorical interpretation enables a multidimensional interpretation of the texts.